Monitoring and Genotyping of Wild Grapevine (Vitis vinifera L. subsp. sylvestris) in Slovenia - Andrej Perko; Oliver Trapp; Erika Maul; Franco Röckel; Andrej Piltaver; Stanko Vršič (Plants, 2024)
Vitis vinifera L. subsp. sylvestris (sylvestris) is the only native wild grapevine in Eurasia (Europe and western Asia) and is the existing ancestor of the grapevine varieties (for wine and table grape production) belonging to the subsp. sativa. In Slovenia, the prevailing opinion has been that there are no Slovenian sylvestris habitats. This study describes sylvestris in Slovenia for the first time and aims to present an overview of the locations of the wild grapevine in the country. In this project, a sample set of 89 accessions were examined using 24 SSR and 2 SSR markers plus APT3 markers to determine flower sex. The accessions were found in forests on the left bank of the Sava River in Slovenia, on the border between alluvial soils and limestone and dolomite soils, five different sites, some of which are described for the first time. The proportion of female to male accessions differed between sites. At two sites, female plants dominated; at others, the ratio was balanced. The plants’ genetic diversity and structure were compared with autochthonous and unique varieties of subsp. sativa from old vineyards in Slovenia and with rootstocks escaped from nature from abandoned vineyards. Sylvestris was clearly distinguishable from vinifera and the rootstocks. Based on genetic analyses, it was confirmed that Slovenian sylvestris is closest to the Balkan and German sylvestris groups. Meanwhile, a safety duplication of the wild grapevine accessions has been established at the University Centre of Viticulture and Enology Meranovo, Faculty of Agriculture and Life Sciences at the University of Maribor.